Shamba Showdown: Ukama Ustawi- Progress Report #6b - Shapiro, Jay; Odera, Denis; Kigo, Samm; Muhoro, Nathan; Girvetz, Evan; Ghosh, Aniruddha (2024)
The fact that Kenya has a youthful population, with a median age of just 19 is well known. Lesser known is that smallshare farmers in the country (who produce 88% of the food in the country) have a median age of 60 and an average life expectancy of just 65 yrs. Shamba Showdown has focussed on the labour shortage this will create from the younger generation not returning to the farm. However, there is a second vector that is potentially even more devastating: The Knowledge Gap. As the older generation dies off, they take with them all of the institutional knowledge, wisdomand experience that typically has an intergenerational transfer from their parents to them, and then from them to their children. Due to the unique youth demographic bulge in Africa, this generation will lose much of that knowledge transfer. Leveraging the latest AI Technology of Retrieval Augmented Generation (RAG’s) we can train virtual elders to be experts in specific fields such as conservation agriculture, beekeeping, sustainable fishing, cooking, etc. These AI experts are then embodied in a relatable elder wise grandparent avatar. Mzee.ai will be a standalone Android App that youth can consult whenever they have a specific question that they would normally ask a parent or community elder. In this way we are taking a unique African approach to blend the age-old concepts of Ubuntu and “it takes a village” with contemporary AI tools to create a “virtual village” preserving knowledge while improving practices.